Crosstalk of four kinds of cell deaths defines subtypes of cutaneous melanoma for precise immunotherapy and chemotherapy - Wan, Qi; Wei, Ran; Wei, Xin; Deng, Ying-ping (Frontiers in Immunology, 2022)
Background: Cell death patterns can give therapeutic and biological clues that facilitates the development of individualized treatments for this lethal form of skin cancer. Methods: We employed unsupervised clustering to establish robust classifications based on the four kinds of cell death-associated gene expression of 462 melanoma patients in the Cancer Genome Atlas (TCGA) and tested their reproducibility in two independent melanoma cohorts of 558 patients. We then used dimensionality reduction of graph learning to display the different characteristics of cell death patterns and immune microenvironment. Results: we examined 570 cell death-associated genes expression data of melanoma patients for exploration, independent verification, and comprehensive classification of 5 reproducible melanoma subtypes (CS1 to 5) with different genomic and clinical features. Patients in death-inactive subtypes (CS1,2, and 5) had the least immune and stromal cells infiltration, and their prognosis was the poorest. A death-active subtype (CS4), on the other hand, had the highest infiltrated immune and stromal cells, and elevated immune checkpoints. As a result, these patients had the highest response of immunotherapy and best prognosis. Additional subtype (CS3) had more diversified cell death and immune characteristics with moderate prognoses. Based on graph learning, we successfully divided the CS3 subtype into two subgroups (group A and group B) with distinct survival outcome, and immune features. Finally, we identified 8 potential chemical drugs were specifically target the therapy of melanoma subtypes. Conclusions: This research defines intrinsic subtypes of melanoma based on crosstalk of four kinds of cell deaths, which affords a blueprint for clinical strategies and guiding precise immunotherapy and chemotherapy for melanoma patients.